Review of the Asian species of the subgenus Neocheilosia Barkalov (Diptera, Syrphidae), with description of new species - Barkalov, Anatolij V.; Ichige, Katsuyoshi (Zootaxa, 2016)
The Asian species of the subgenus Neocheilosia are reviewed. A new species Cheilosia (Neocheilosia) shiranesana Barkalov & Ichige sp. n. is described, and Cheilosia mutini Barkalov is synonymized with Cheilosia komabaensis Shiraki syn. n. A listing of the five Asian species of the subgenus,information on their distribution and an illustrated identification key is provided.